Impact of difficult-to-treat depression for patients and society: a real-world study - Benavente, Sergio; Parra, Alba; Lopez-Castroman, Jorge; Conejero, Ismael; Alonso-Torres, Pablo; López, Tatiana Caraballo; Carrasco Arteaga, Pablo; Baca-García, Enrique (Frontiers in Psychiatry, 2025)
BackgroundTreatments and evolution of depressive disorders are highly heterogeneous, with difficult-to-treat depression (DTD) presenting elevated medical and economic burdens, particularly when accompanied with suicidality. This study analyzed clinical profiles, evolution, and costs associated with major depressive disorder (MDD), MDD with suicide risk (MDD-SR), DTD, and DTD with suicide risk (DTD-SR) over 12 months, considering initial healthcare pathways.MethodsA cohort of 3,941 individuals aged ≥18 years was recruited between 2014 and 2018 in four Madrid hospitals. Patients were classified according to their first contact with mental health services through emergency settings (emergency-first) or outpatient settings (outpatient-first). Sociodemographic data, International Classification of Diseases (ICD-10) diagnoses, and healthcare resource use were extracted from electronic health records and the MeMind digital ecosystem. Suicide risk was assessed using the Mini International Neuropsychiatric Interview (MINI)-based suicide risk assessment, and clinical profiles and costs were compared.ResultsCompared with outpatient-first patients, emergency-first patients showed greater depression severity, psychiatric comorbidities, and suicide risk (p < 0.001), along with increased rates of DTD (p = 0.021), poorer treatment outcomes, and higher global costs. Patients with DTD or suicide risk displayed greater depression severity, lower treatment response, more frequent relapses, psychiatric hospitalization, and antidepressant augmentation strategies compared to MDD-only patients. Emergency-first DTD-SR patients incurred the highest costs (€15,358.1 [SD = 16,415.1]/patient/year). Suicide risk was strongly associated with probable relapses and DTD.ConclusionsDespite the high economic burden, important needs remain unmet for DTD, especially for patients showing suicide risk with a first contact through the emergency setting. Earlier detection, innovative treatments, improved access to healthcare, and integration in mobile health programs should mitigate these gaps and improve clinical outcomes in this vulnerable population.